Association of Quality of Life Measures and Otolaryngologic Care in Cystic Fibrosis Patients. (August 2022) - Leong, Stephen; Sharma, Rahul K.; Safi, Chetan; DiMango, Emily; Keating, Claire; Gudis, David A.; Overdevest, Jonathan B.
Objectives: Appropriate management of chronic rhinosinusitis (CRS) among patients with cystic fibrosis (CF) is important in improving quality of life. Otolaryngologists play a critical role in reducing CRS symptom burden. This study seeks to evaluate the role of patient-reported quality-of-life measures in guiding interventions for CF-related sinus disease. Methods: We performed a prospective, cross-sectional study of 105 patients presenting to a CF-accredited clinic between July and September 2018. Demographic data and sinus surgery history were collected, in addition to Sino-Nasal Outcome Test (SNOT-22) and Questionnaire of Olfactory Disorders (QOD-NS) scores. Statistical analysis was conducted using correlation and non-parametric Mann-Whitney U tests. Results: Baseline well-care visits accounted for 71.4% of all clinical evaluations. Prior otolaryngology intervention was noted in 69 (66%) patients, where the majority of these patients (63/69; 91%) underwent endoscopic sinus surgery (ESS). Patients with a history of otolaryngology intervention had an average SNOT-22 score of 33.2 (SD = 20.6) compared to 24.9 (SD = 18.5) for patients without prior intervention ( P = .048). The average QOD-NS score was 5.5 (SD = 6.4) among patients referred to otolaryngologists and 3.1 (SD = 5.7) for non-referred patients ( P = .012). SNOT-22 and QOD-NS scores were modestly correlated ( R of .43). Conclusion: CF patients with symptoms resulting in worse quality-of-life assessments were more likely to have established coordinated care with an otolaryngologist. Further validation of the utility of SNOT-22 and QOD-NS questionnaires as care coordination metrics is necessary in the CF population.